Bridging Innovation to Prevent Ventilator-Associated Pneumonia: A Descriptive Qualitative Study among Critical Care Nurses - Yulis Setiya Dewi; Arina Qona'ah; Hidayat Arifin; Rifky Octavia Pradipta; Rosita Rosita; Lizy Sonia Benjamin (Jurnal Keperawatan Padjadjaran, 2021)
Background: Ventilator-Associated Pneumonia (VAP) is still a concern for individuals who are dependent on a ventilator. It is envisaged that the growth of technology-based innovations would lead to the creation of remedies for the prevention of VAP. Purpose: The purpose of this study was to learn more about ICU nurses’ perspectives on nursing innovations to avoid VAP in patients who are on ventilators. Methods: Throughout July and August of 2021, a descriptive qualitative research study was conducted. Through the use of the snowball sampling approach, a total of 30 critical care nurses were recruited. During the interview procedure, each participant had around 40 minutes of time for an in-depth interview using a semi-structured format. In order to analyse the findings of the interviews, the technique proposed by Colaizzi was used. Results: The following four themes emerged: 1) Development of tools to prevent infection, 2) Innovation to monitor cuff tension, 3) Improvement of nurses’ skills and knowledge in using technology, and 4) Nurses’ burden in using technology. Conclusion: Nurses may benefit from considering VAP management as a part of technology-based innovation strategy. Nurses have praised the invention for measuring and monitoring the ETT cuff as a source of optimism for future advancement.